The Trail of Tears : [videorecording (DVD)] : Cherokee legacy - Richie, Chip; Jones, James Earl; Studi, Wes; Garner, James. 1928-2014 (Rich-Heape Films, 2006)
Documents the forced removal in 1838 of the Cherokee Nation from the southeastern United States to Oklahoma. Shows the suffering endured by the Cherokees as they lost their land and the difficult conditions they endured on the trail. Describes how thousands of Cherokees died during the Trail of Tears, nearly a quarter of the nation, including most of their children and elders.